Implantação de matas ciliares por plantio direto utilizando-se semente peletizadas - Almeida, Narrúbia Oliveira de (2004)
Traditionally the introduction ofprotected forests has been accomplished by using seedling. However, studies have indicated the viability of using direct sowing offorest tree seeds for this purpose. When the topographical conditions allow the sowing procedure may be performed mechanically. For establishment of a new protect área there is a need ofworking with a diversity ofspecies, which also present diversity inseed format and size, creating difficulties for the mechanized sowing operatíon. In this sense, seed pelleting is a technique that allows unifonnization of seed size and format. Therefore, this work had the objectives to test products used in the process ofseed pelleting to evaluate the efFects ofseed pelleting on seedling emergence and plant growth and evaluate the viability of seed pelleting on the establishment of protected forest by mechanical sowing. Twelve forest tree species representing three ecological groups were used in this study: Cedrella fissilis, Copaifera langsdorffii, Enterolobium contortisiliquum, Guazuma ulmifolia, Lithraea molleoides, Piptadenia gonoacantha, Senna macranthera, Senna multijuga, Sesbania virgata, Solanum granulaç-leprosum, Tabebuia serratifolia and Dieresis micrantha. Four experimente were done inthe laboratory, two inthe green house and one in the field. Several glue and stuffing material were tested for making the pellet, the effect ofthe fertilizer used in the pellet and the effect ofme pellet size. Inthe field was tested theeffect ofplant population andgrow on 0,4 m, 0,7 m and 1,0 m spacing managed by weeding, by pre emerging herbicide and wimess, in this case using the best results obtained at green house. The laboratory and green house experiments were set in DIC and field experiment was set inDBC, arranged insub-divided parcel and evaluated during 11 months. Adhesive and stuffing materiais tested were the PVA glue (Cascorez-extra) ina concentration of 20%, fine sand and a mixture composed of sand + micro cellulose + explosol (4:2:1 v/v). The use ofsand + micro cellulose + explosol (4:2:1 v/v) showed the best results. The use ofsimple super phosphate and triple super phosphate as part ofthe pellet composition in aconcentration of50% and 100% for both sources, affected negatively the percentage ofseedling emerged but favored the growth of seedlings of Guazuma ulmifolia. Increasing lhe thickness ofthe seed pellet affected negatively seedling emergence; the majority ofthe species presented emergence and index ofemergence in green house smaller than the results obtained in the laboratory. In the field, exception for Lithraea molleoides, the species showed seedling emergence; however, the obtained values were inferior to the values obtained in laboratory and green house. In spacing of 0,4 m and in the parcels managed by weeding were observed the largest number of plant population/ha and largest growth in average; the use ofpre emerging herbicide was efficient in minimizing the occurrence of weed plants, however its efficiency was affected by the aggressiveness ofthe existing braquiária. The percentage ofpioneering, clímax light demanding and climax shade tolerant species after 11 months ofsowing was 69,46%, 18,68% and 11,85% respectívely. Sesbania virgata, Enterolobium contortisiliquum and Copaifera langsdorffii were the species that presented highest numberofseedlingemergency in the field. Sesbania represented 54,2% ofthe total number ofplants after 11 months. The médium mortality observed was 11,77% when the field was managed by weeding, 25,69% when manage by pre emerging herbicide and 24,67% in the witness, generatíng an average of 20,71%. Cedrella fissilis, Piptadenia gonoacantha, Tabebuia serratifolia and Copaiferalangsdorffii with 68,6%, 53,3%, 48,6% and36,5%, respectívely were the species that presented the highest mortality values and slowest growth, probably due to the competítion with braquiária and deficiency ofwater in a period before seedling emergence. The plant population/ha after 11 months of sowing when field was managed by weeding, pre emerging herbicide and witness was 24.073, 16.115 and 20.269, respectívely. The plant population /ha after 11 months ofsowing in 0,4 m, 0,7 m, and l,0m spacing was 29.680,16.161 and 14.615, respectívely. The results obtained here confirmed the efficiency of seed pelletingand mechanized sowing in the establishment of protected riparian forest.